MORPHOLOGICAL AND BIOCHEMICAL RESPOSES OF COW PEA (CV. PUSA BARSATI) GROWN ON FLY ASH AMENDED SOIL IN PRESENCE AND ABSENCE OF MELOIDOGYNE JAVANICA AND RHIZOBIUM LEGUMINOSARUM - Singh, Kamal; Khan, A. A.; Khan, Iram; Rizvi, Rose; Saquib, M. (Ecoprint: An International Journal of Ecology, 2011)
Plant growth, yield, pigment and protein content of cow-pea were increased significantly at lower levels (20 and 40%) of fly ash but reverse was true at higher levels (80 and 100%). Soil amended by 60% fly ash could cause suppression in growth and yield in respect to 40% fly ash treated cow-pea plants but former was found at par with control (fly ash untreated plants). Maximum growth occurred in plants grown in soil amended with 40% fly ash. Nitrogen content of cow-pea was suppressed progressively in increasing levels of fly ash. Moreover, Rhizobium leguminosarum influenced the growth and yield positively but Meloidogyne javanica caused opposite effects particularly at 20 and 40% fly ash levels. The positive effects of R. leguminosarum were marked by M. javanica at initial levels. However, at 80 and 100% fly ash levels, the positive and negative effects of R. leguminosarum and/or M. javanica did not appear as insignificant difference persist among such treatments. Key words: Meloidogyne javanica; Rhizobium leguminosarum; Fly ash; Growth; Yield DOI: 10.3126/eco.v17i0.4098 Ecoprint An International Journal of Ecology Vol. 17, 2010 Page: 17-22 Uploaded date: 28 December, 2010